Additive-manufactured ceramics for dental restorations: a systematic review on mechanical perspective - Lu, Yuqing; van Steenoven, Anouk; Dal Piva, Amanda Maria de Oliveira; Tribst, João Paulo Mendes; Wang, Li; Kleverlaan, Cornelis J.; Feilzer, Albert J. (Frontiers in Dental Medicine, 2025)
BackgroundAdditive manufacturing (AM) is rapidly expanding as a substitute for conventional heat-pressing and milling techniques for ceramic restorations. However, experimental and clinical evidence on the mechanical properties and performance of the final ceramic products is yet insufficient. This systematic review aimed to update the latest advances in additive manufacturing of restorative ceramics with a focus on their mechanical properties.MethodsThis systematic review was structured using the 5-step methodology based on the research question: what are the mechanical properties of additive-manufactured restorative ceramics in comparison with subtractive manufacturing? The electronic literature search was performed independently by 2 authors in the following databases: PubMed/MEDLINE, Web of Science, and Scopus. Published articles from 2019 to 2023 were screened, analysed and the relevant papers were selected for inclusion in this review.ResultsA total of 40 studies were included. The available ceramics include zirconia, alumina and alumina-zirconia composites, lithium disilicate, porcelain and fluorapatite glass ceramic. The mechanical properties were summarized according to material and technique: density (15 studies), flexural strength (31 studies), fracture toughness (7 studies), Young's modulus (7 studies), hardness (11 studies) and performance (7 studies). Overall, the properties exhibited an upward trend toward the values of conventional techniques. Typical processing defects, including porosity, agglomerates, cracks, surface roughness, and other defects, were also analyzed.ConclusionsWith significant technological advancements, the mechanical properties of AM ceramics have come close to ceramics by conventional manufacturing, whereas their reliability, the influence of printing layer orientations, and long-term performance still need further investigation.